Myosin Heavy Chain Converter Domain Mutations Drive Early-Stage Changes in Extracellular Matrix Dynamics in Hypertrophic Cardiomyopathy - Hsieh, Jeanne; Becklin, Kelsie L.; Givens, Sophie; Komosa, Elizabeth R.; Lloréns, Juan E. Abrahante; Kamdar, Forum; Moriarity, Branden S.; Webber, Beau R.; Singh, Bhairab N.; Ogle, Brenda M. (Frontiers in Cell and Developmental Biology, 2022)
More than 60% of hypertrophic cardiomyopathy (HCM)-causing mutations are found in the gene loci encoding cardiac myosin-associated proteins including myosin heavy chain (MHC) and myosin binding protein C (MyBP-C). Moreover, patients with more than one independent HCM mutation may be at increased risk for more severe disease expression and adverse outcomes. However detailed mechanistic understanding, especially at early stages of disease progression, is limited. To identify early-stage HCM triggers, we generated single (MYH7 c.2167C>T [R723C] with a known pathogenic significance in the MHC converter domain) and double (MYH7 c.2167C>T [R723C]; MYH6 c.2173C>T [R725C] with unknown significance) myosin gene mutations in human induced pluripotent stem cells (hiPSCs) using a base-editing strategy. Cardiomyocytes (CMs) derived from hiPSCs with either single or double mutation exhibited phenotypic characteristics consistent with later-stage HCM including hypertrophy, multinucleation, altered calcium handling, metabolism and arrhythmia. We then probed mutant CMs at time points prior to the detection of known HCM characteristics. We found MYH7/MYH6 dual mutation dysregulated extracellular matrix (ECM) remodeling, altered integrin expression, and interrupted cell-ECM adhesion by limiting the formation of focal adhesions. These results point to a new phenotypic feature of early-stage HCM and reveal novel therapeutic avenues aimed to delay or prohibit disease onset.